National Housing Authority Projects in the Philippines: A Structured Narrative Literature Review and Policy Implications - Emil Arca (Transpublika Publisher, 2026)
The National Housing Authority (NHA) plays a pivotal role in delivering public housing programs in the Philippines; however, existing evidence on program implementation remains fragmented across diverse geographical settings, policy contexts, and methodological approaches, limiting an integrated understanding of the factors shaping housing outcomes. This study synthesizes the literature on NHA housing projects to examine recurring implementation patterns and develop evidence-informed policy implications for strengthening public housing governance. A structured narrative literature review, guided by the PRISMA 2020 reporting framework, was undertaken to identify, screen, and synthesize 22 relevant studies published between 2016 and 2026. The included literature was analyzed using thematic synthesis to integrate evidence across heterogeneous research designs. The thematic synthesis generated seven interrelated analytical themes: the evolution of NHA programs, housing quality and physical infrastructure, beneficiary satisfaction and residential well-being, livelihood and economic opportunities, accessibility to essential services, governance and community participation, and implementation challenges. Governance functions as the integrating mechanism linking housing quality, service accessibility, livelihood opportunities, and community participation, while challenges arise from systemic institutional and socioeconomic constraints rather than isolated operational deficiencies. These findings suggest that the effectiveness of NHA housing programs depends on integrated policy implementation that aligns physical infrastructure with governance capacity, socioeconomic development, and long-term community sustainability. By consolidating fragmented evidence into a coherent framework, this review provides a stronger conceptual foundation for evidence-informed housing policy, public housing governance, and future research on NHA programs in the Philippines.